New decentralised event-triggered consensus strategy for single and double integrator multi-agent systems - Aggarwal, S.; Goyal, J.K.; Tr, S.; Ghosh, S.; Kamal, S.; Dworak, P. (Institute of Electrical and Electronics Engineers Inc., 2020)
This paper proposes new decentralised event-triggering conditions for single- and double integrator multi-agent systems. The developed conditions are based on the relative ratio of the state measurement error and norm of a state function for actuating the controller updates. With higher limits on the maximum tolerable state measurement error, the controller is shown to reduce the actuation updates and hence, the use of available resources. The network topology is assumed to be undirected and connected. The inter-event intervals are shown to be strictly positive for all agents to eliminate the zeno phenomenon. The theoretical concepts are further demonstrated through numerical comparisons and illustrative simulations. © 2013 IEEE.
Keywords: Decentralised event-triggered control; inter-event interval; multi-agent systems; zeno phenomenon